2002
DOI: 10.1055/s-2002-35258
|View full text |Cite
|
Sign up to set email alerts
|

A Score Card for Upper GI Endoscopy: Evaluation of Interobserver Variability in Examiners with Various Levels of Experience

Abstract: As expected with scores involving subjective assessment of performance, the variability between reviewers was substantial. Nevertheless, the assessment score was capable of distinguishing reliably between different experience levels in terms of a good individual observer consistency. The score card can therefore be used to document both training status and progress during endoscopy training courses using bio-simulation models, and this might be able to provide improved quality assurance in GI endoscopy trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…The parameters of this scale were initially described and validated by Reznick et al [19] and were specifically modified for the purpose of evaluating endoscopic skills. In its current form, it has not been validated as an assessment tool, but it has previously been found that interobserver agreement is good when equally experienced observers evaluate the performance of trainees on endoscopic and laparoscopic tasks [10,17]. Since we acquired the data reported in the present study, other scoring systems for endoscopy have been proposed and evaluated [18].…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of this scale were initially described and validated by Reznick et al [19] and were specifically modified for the purpose of evaluating endoscopic skills. In its current form, it has not been validated as an assessment tool, but it has previously been found that interobserver agreement is good when equally experienced observers evaluate the performance of trainees on endoscopic and laparoscopic tasks [10,17]. Since we acquired the data reported in the present study, other scoring systems for endoscopy have been proposed and evaluated [18].…”
Section: Discussionmentioning
confidence: 99%
“…Previous attempts at objective assessment using score card OGD based on video reviews of endoscopies in biosimulation (the Erlangen Endo-Trainer) model revealed substantial inter-observer variability. 56 Many of the current training programmes for nurse endoscopists utilise video reviews of endoscopic procedures to assess performance of nurse endoscopists and certify them competent.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal assessment method would be one that is blinded and objective. One such method has been developed, but was found to have poor interobserver reliability [9]. Further work is being undertaken to validate the blinded VES assessment in real procedures before it is used to demonstrate the effect of training on the simulator.…”
Section: Discussionmentioning
confidence: 99%